Naturally Occurring TPE-CA Maintains Gut Microbiota and Bile Acids Homeostasis via FXR Signaling Modulation of the Liver–Gut Axis - Liu, Linlin; Liu, Zhenli; Li, Hui; Cao, Zhiwen; Li, Wen; Song, Zhiqian; Li, Xiang; Lu, Aiping; Lu, Cheng; Liu, Yuanyan (Frontiers in Pharmacology, 2020)
Antibiotics-induceds changes in intestinal flora (dysbiosis) may have various effects on the host. Dysbiosis is associated with numerous metabolites including bile acids, which are produced in the liver from cholesterol and metabolized in the gut by intestinal microbiota. Total phenolic extracts of Citrus aurantium L. (TPE-CA) are rich in dietary flavanones and their glycosyl derivatives, including flavones, flavonols, polymethoxyflavones and coumarins, which exert positive health effects on the microbiota. The aim of this study is to elucidate the interplays between the intestinal microbiota and bile acids metabolism attributed to antibiotics. Mice were exposed to broad-spectrum antibiotics, such as ampicillin, streptomycin and clindamycin, for 14 days. This exposure resulted in reduced bacterial diversity and richness, and destroyed intestinal permeability. The homeostasis of bile acids was also affected. Subsequent TPE-CA administration, counteracted most of the dysbiosis, and reshaped intestinal permeability, these effects occurred via upregulation of zonula occludens 1 and occludin associated proteins and downregulation of serum endotoxin compared to the antibiotics group. TPE-CA maintained the homeostasis of bile acids via modulation of the liver -gut axis related farnesoid X receptor (FXR)/ fibroblast growth factor 15 (FGF15) pathway and FXR-targeted protein. Our findings indicated that TPE-CA exerted a protective effect on the restoration of intestinal microbiota composition, reshaped barrier integrity and maintained bile acid homeostasis via the liver - gut axis with antibiotics-induced dysbiosis.